ANALISIS KINERJA EKSPOR PADA PERUSAHAAN KELUARGA - Winarsih, Fiqih Puji; Raharjo, Susilo Toto (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
Family companies are companies where the majority of owners are family, where the applicable provisions are produced by part of the organization that is emotionally bound. In the period 2015-2018 PT. Alamanda, which is an export company for commodity X, experienced a decline in production performance. In this case the researcher wants to know things that affect production performance so that the company experiences a decline in the number of exports of commodity X. This study uses a qualitative method with a case study approach by analyzing actual events in the company with the subject being each individual who is related to the course of the business. from downstream to upstream. Collecting data using in-depth interviews conducted directly or online to participants and supported by direct observations in the company environment. The results of the study show that in addition to technical and non-technical factors, the decline in PT Alamanda's production performance is influenced by purchasing decisions that are not fast in the field. Competition is a very natural thing to happen, but anticipation in competition and changes in strategy need to be done quickly. Innovation in the commodity supply chain system is also very influential in controlling the purchase price in order to minimize the auction price of commodity X.